1994
DOI: 10.1177/014272379401404001
|View full text |Cite
|
Sign up to set email alerts
|

Developmental relationships between production and comprehension of mental terms

Abstract: Mental terms, including belief and desire terms, were studied in a sample of 14 mother-child pairs longitudinally when the children were 2;0, 3;0, and 4;0 in order to examine the acquisition of these terms. Percentage use of utterances involving belief and desire terms in naturalistic interactions were calculated for each subject. In addition, children at 4;0 were tested for comprehension of the distinctions between the belief terms know, think and guess, using a task designed to assess the understanding of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 27 publications
1
48
1
2
Order By: Relevance
“…On a general level, mothers use more desire terms than belief terms when their children are two-years-old, but steadily increase their frequency of use of belief terms over the course of the next year, mirroring the children's increased use (Beeghly, Bretherton & Mervis, 1986;Moore, Furrow, Chiasson & Patriquin, 1994;Jenkins, Turrell, Kogushi, Lollis & Ross, 2003). More specifically, mothers' frequency of use of belief words when their children were two years of age predicted the children's frequency of use at the ages of two, three, and four years, as well as their mental verb comprehension at age four (Jenkins et al, 2003;Moore et al, 1994), and mothers' use of mental terms for true mental reference when children were age two predicted the children's use of such words in these same functions when they were age three (Furrow et al, 1992). Relatedly, Ruffman et al (2002) have reported that mothers' frequency of mental state utterances was a strong predictor of their children's theory of mind performance across the age range of three to five years.…”
Section: Environmental Influences On MV Developmentmentioning
confidence: 99%
“…On a general level, mothers use more desire terms than belief terms when their children are two-years-old, but steadily increase their frequency of use of belief terms over the course of the next year, mirroring the children's increased use (Beeghly, Bretherton & Mervis, 1986;Moore, Furrow, Chiasson & Patriquin, 1994;Jenkins, Turrell, Kogushi, Lollis & Ross, 2003). More specifically, mothers' frequency of use of belief words when their children were two years of age predicted the children's frequency of use at the ages of two, three, and four years, as well as their mental verb comprehension at age four (Jenkins et al, 2003;Moore et al, 1994), and mothers' use of mental terms for true mental reference when children were age two predicted the children's use of such words in these same functions when they were age three (Furrow et al, 1992). Relatedly, Ruffman et al (2002) have reported that mothers' frequency of mental state utterances was a strong predictor of their children's theory of mind performance across the age range of three to five years.…”
Section: Environmental Influences On MV Developmentmentioning
confidence: 99%
“…While this sort of teaching makes sense, it typically generates little more than the children's ability to produce the right answer. It's unlikely that such teaching leads children to form personal beliefs that they are truly responsible for their behavior (see Dunn et al 1991;Moore et al 1994).…”
Section: Complex Causality Can Be Self-discovered Through Dialoguementioning
confidence: 99%
“…We started by translating the English terms identified in the J. study, which for the purpose of the J. study had been derived by collecting all the terms from previous observational studies of children's mental state talk (Shatz et al 1983;Dunn et al 1987;Dunn et al, 1991;Perner, 1991;Moore et al 1994;Bartsch andHughs andDunn, 1999). Talk about the mind can be assessed based on different criteria.…”
Section: Coding Of Mental State Termsmentioning
confidence: 99%